Ecosystem Protection Curriculum Model with Passive Defense Approach - Ahmadizadeh, Maryam; Esmaeilishad, Behrang; Soleimanpour Omran, Mahboube; Banagar, Gholamreza (International Journal of Education and Cognitive Sciences, 2022)
The aim of the study was to present a curriculum model for ecosystem protection with a passive defense approach. This research was conducted using a qualitative synthesis method, and the research environment included all Iranian articles (2009-2023) and international articles (2007-2023). A purposive sampling method was applied until data saturation was reached, resulting in the selection of 62 articles. The research instrument was the reading of article texts. Data analysis was carried out based on a classification system of open concepts, organizing concepts, and comprehensive concepts. The results showed that the curriculum model for ecosystem protection with a passive defense approach in the four areas of objectives, methods, content, and activities is as follows: in the dimension of objectives, it includes 6 components (cognitive, affective, psychomotor, metacognitive, meta-affective, and meta-psychomotor); in the dimension of content, it includes 4 components (content organization, content contextualization, content revision, and content integration); in the dimension of methods, it includes 6 components (self-directed learning, self-regulated learning, systemic learning, multiple learning, practical learning, and motivational learning); and in the dimension of activities, it includes 5 components (environmental-centered, exploratory, research-based, dialogic, and contingent).